Optimasi Mutu Hafalan Al-Qur'an melalui Manajemen Mulazamah Berbasis Kemitraan di Pendidikan Dasar - Siwi Utami; Dahlia (MUADDIB: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the management of the Mulazamah class program in improving the quality of Qur’an memorization at MI Tahassus Prapag Kidul, Purworejo. The Mulazamah class is an intensive tahfidz program designed to produce students with mutqin (well-established) memorization, characterized by fluency, accurate makharijul huruf (articulation points), precise tajweed, and high retention. This study employed a descriptive qualitative approach, utilizing interviews, observations, and documentation for data collection. Informants included the head of the madrasah, Mulazamah class teachers, parents, and students. The results demonstrate that the program’s management is systematically executed based on Terry & Rue (2019) management functions planning, organizing, actuating, and controlling. Planning involves setting objectives, determining memorization targets, selecting learning methods, and establishing rigorous student-parent admission criteria. Organizing is implemented through a clear division of responsibilities among the madrasah leadership, tahfidz teachers, and parents. Actuating is carried out intensively through classical tahfidz learning, routine muroja’ah, ziyadah (memorization deposits), spiritual habituation, and nutritional support. Controlling is conducted through periodic evaluations, tasmi’ examinations, systematic progress logging in mutaba’ah books, parental reporting, and corrective follow-ups through tahfidz clinics. These management practices significantly contribute to improving students' memorization quality, enabling them to achieve the Mumtaz (excellent) standard set by the madrasah.